Implementasi Manajemen Kesiswaan dalam Membangun Budaya Sekolah yang Religius dan Berintegritas di SMK Bina Sejahtera 3 Kota Bogor - Salisa Syifa Asyafia; M. Hidayat Ginanjar; Heriansyah (La-Tahzan: Jurnal Pendidikan Islam, 2026)
The development of religious character and integrity is a crucial necessity in vocational schools, as students are prepared to enter the workforce where discipline, ethics, and high responsibility are essential. SMK Bina Sejahtera 3 Kota Bogor was selected as the research site because it is a school with a large student population, a strong religious culture, and a well-established, structured, and continuous student management system, making it highly relevant as a case study. This study aims to describe the implementation of character-based student management in fostering a religious culture and student integrity. A qualitative approach with a case study method was employed through in-depth interviews, participatory observations, and document analysis. The findings indicate that student management is carried out in an integrated manner through planning, implementation, and supervision. Religious habituation programs such as morning Quran recitation, congregational prayers, and daily sermons strengthen students’ spiritual discipline, while the point-based violation system, case conference, and application-based attendance monitoring cultivate responsibility and self-control. Extracurricular activities such as Scouts, Islamic student organizations, and social-religious programs develop leadership, cooperation, and empathy. These findings affirm that character-based student management effectively builds a school culture that is religious, disciplined, and integrity-driven.